Development of a Heyzine Flipbook Media Integrated with Problem-Based Learning to Improve Natural and Social Learning Outcomes of Elementary School Students - Anggono, Wisnu Aji Suryo; Setiawan, Deni (FKIP Universitas Lampung, 2025)
This study aims to develop and test the effectiveness of Heyzine Flipbook learning media integrated with the Problem-Based Learning model to improve the learning outcomes of natural and social sciences of grade V elementary school students. This development is motivated by the lack of effectiveness of conventional media and the complexity of natural and social science materials that require innovative and interactive media. This research uses the Research and Development (RnD) method of the Borg & Gall model, consisting of 10 stages. The research was conducted in two stages: development and testing. The development stage includes problem analysis and literature study, initial development of Heyzine Flipbook media, expert validation, and revision. The pilot stage tested the effectiveness of the media on 49 fifth-grade students of Bunayya Integrated Islamic Elementary School. Initial data collection includes documentation, interviews, questionnaires, and observations. The instruments used in this study include pretest-posttest to test the effectiveness of the media and expert validation to test the feasibility of the media developed. Data analysis used a T-test, Effect Size Cohen's d and N-Gain. The results of expert validation showed that Heyzine Flipbook media was very feasible to use, with an average score of 93.5%. The effectiveness test showed a significant difference between the pretest and posttest (0.000 <0.05). The effectiveness level of Cohen's Effect Size d reached 1.767 on a small scale and 2.112 on a large scale, significantly improving learning outcomes. The N-Gain average improvement test reached 0.5537 on a small scale with a medium category and 0.5503 on a large scale with a medium category. This proves that Heyzine Flipbook media integrated with Problem-Based Learning is effective in helping students understand the material on Indonesia's location and geographical conditions. Based on the study results, Heyzine Flipbook media is recommended for learning natural and social sciences in elementary school. This media is an interesting and innovative alternative to conventional media. Researchers recommend that heyzine flipbook media integrated with problem-based learning models be applied to learning, especially in class V, to create meaningful learning. Keywords: media development, heyzine flipbook, learning model, learning outcomes.